Dispersions of Hollow and Bamboo-Like Multiwalled Carbon Nanotubes in Polyethyleneimine: Critical Analysis of the Preparation Conditions and Applications for Electrochemical Sensing - Eguilaz Rubio, Marcos (2014)
This work is focused on the critical analysis of the influence of the experimental conditions on the efficient dispersion of hollow-type (hMWCNT) and bamboo-like (bMWCNT) multiwall carbon nanotubes with polyethyleneimine (PEI). Spectroscopic and electrochemical studies demonstrated that the adequate combination of optimized ultracavitation and centrifugation is essential to obtain successful dispersions. The selected conditions were 1.0 mg mL−1 hMWCNT in 3.0 mg mL−1 PEI sonicated with a sonicator probe operating at 50 % of amplitude for 300 s and centrifuged at 9000 rpm for 15 min. Bamboo-like multiwall carbon nanotubes were faster exfoliated and glassy carbon electrodes (GCE) modified with the resulting dispersion allowed the amperometric detection of hydrogen peroxide at lower potentials (0.100 V) with a detection limit of 5.5 µM.